2016
DOI: 10.1021/jacs.6b07396
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Both Retention and Inversion Pathways in Stereospecific, Nickel-Catalyzed Miyaura Borylations of Allylic Pivalates

Abstract: We have developed a stereospecific, nickel-catalyzed Miyaura borylation of allylic pivalates, which delivers highly enantioenriched α-stereogenic γ-aryl allylboronates with good yields and regioselectivities. Our complementary sets of conditions enable access to either enantiomer of allylboronate product from a single enantiomer of readily prepared allylic pivalate substrate. Excellent functional group tolerance, yields, regioselectivities, and stereochemical fidelities are observed. The stereochemical switch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 57 publications
2
58
0
1
Order By: Relevance
“…Chiral organoboronates are of significant utility in asymmetric synthesis for constructing a wide range of other functional groups through C-B bond transformation in a stereospecific fashion 35 , 36 . To date, several strategies 37 , such as stereospecific organoboronate homologation 38 , 39 , borylation of benzylic electrophiles 40 , 41 , asymmetric hydrogenation of alkenylboronic esters 42 , 43 , and asymmetric hydroboration of alkenes 44 53 , have been developed for construction of chiral secondary organoboronates. However, asymmetric hydroboration of a mixture of alkenes isomers to deliver chiral products has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral organoboronates are of significant utility in asymmetric synthesis for constructing a wide range of other functional groups through C-B bond transformation in a stereospecific fashion 35 , 36 . To date, several strategies 37 , such as stereospecific organoboronate homologation 38 , 39 , borylation of benzylic electrophiles 40 , 41 , asymmetric hydrogenation of alkenylboronic esters 42 , 43 , and asymmetric hydroboration of alkenes 44 53 , have been developed for construction of chiral secondary organoboronates. However, asymmetric hydroboration of a mixture of alkenes isomers to deliver chiral products has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral tertiary allylboronates are useful synthetic building blocks, [1][2][3] and the boryl-substituted stereocenters can be transformed into diverse chiral quaternary motifs or be utilized to form homoallylic alcohols or amines by allylboration. While there are amyriad of approaches to synthesizing chiral secondary allylboronates, [4][5][6][7][8][9][10][11][12] ranging from hydroboration to conjugated borylation, direct access to tertiary ones is still very limited (Scheme 1). By using enantioenriched secondary alcohols,t he corresponding vinyl-substituted tertiary allylboronates can be prepared through al ithiation/ borylation approach (Scheme 1a).…”
mentioning
confidence: 99%
“…Watson and co-workers have recently shown that nickel catalysis can be used to effect the stereospecific borylation of g-aryl allylic pivalates with B 2 pin 2, providing a-stereogenic garyl allylic boronic esters in high levels of enantioselectivity (Scheme 25). [87] Interestingly,t he stereospecificity of the substitution could be inverted through ac hange in solvent: in non-polar solvents,h igh levels of stereoretention is observed, while in polar solvents,s uch as acetonitrile,t he allylic boronic esters are obtained with stereoinversion. The authors propose am echanism involving a p-allyl nickel intermediate,w hich undergoes regioselective and stereoretentive reductive elimination.…”
Section: Angewandte Chemiementioning
confidence: 99%